2011
DOI: 10.4174/jkss.2011.81.suppl1.s85
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cyst with ectopic distal location of the papilla of Vater

Abstract: In cholangiographic techniques, the close relationship between choledochal cyst and anomalous union of pancreaticobiliary duct has attracted medical attention. There have been rare cases in which the papilla of Vater was found in a position other than its normal position, and such cases have been reported sporadically. However, such cases are interesting in the anatomical context. In this review, we present our experience of choledochal cyst in a 30-month-old boy in whom the papilla of Vater was positioned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…found that 67.8% (82/121) of children with CC who underwent ERCP had a distal opening of the major papilla to the descending duodenum [ 22 ]. Additionally, two studies reported that some patients with HDP were complicated by APBJ [ 23 , 24 ]. At present, the mechanism underlying the association between HDP and congenital abnormalities of the pancreaticobiliary duct remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…found that 67.8% (82/121) of children with CC who underwent ERCP had a distal opening of the major papilla to the descending duodenum [ 22 ]. Additionally, two studies reported that some patients with HDP were complicated by APBJ [ 23 , 24 ]. At present, the mechanism underlying the association between HDP and congenital abnormalities of the pancreaticobiliary duct remains unclear.…”
Section: Discussionmentioning
confidence: 99%